Loss of individualized behavioral trajectories in adult neurogenesis‐deficient cyclin D2 knockout mice. Issue 4 (7th March 2023) - Lopes, Jadna Bogado; Małz, Monika; Senko, Anna N.; Zocher, Sara; Kempermann, Gerd
Abstract: There is still limited mechanistic insight into how the interaction of individuals with their environment results in the emergence of individuality in behavior and brain structure. Nevertheless, the idea that personal activity shapes the brain is implicit in strategies for healthy cognitive aging as well as in the idea that individuality is reflected in the brain's connectome. We have shown that even isogenic mice kept in a shared enriched environment (ENR) developed divergent and stable social and exploratory trajectories. As these trajectories—measured as roaming entropy (RE)—positively correlated with adult hippocampal neurogenesis, we hypothesized that a feedback between behavioral activity and adult hippocampal neurogenesis might be a causal factor in brain individualization. We used cyclin D2 knockout mice with constitutively extremely low levels of adult hippocampal neurogenesis and their wild‐type littermates. We housed them for 3 months in a novel ENR paradigm, consisting of 70 connected cages equipped with radio frequency identification antennae for longitudinal tracking. Cognitive performance was evaluated in the Morris Water Maze task (MWM). With immunohistochemistry we confirmed that adult neurogenesis correlated with RE in both genotypes and that D2 knockout mice had the expected impaired performance in the reversal phase of the MWM. But whereas the wild‐type animals developed stable exploratory trajectories with increasing variance, correlating with adult neurogenesis, this individualizing phenotype was absent in D2 knockout mice. Here the behaviors started out more random and revealed less habituation and low variance. Together, these findings suggest that adult neurogenesis contributes to experience‐dependent brain individualization.